Rancang Bangun Game Edukasi Pengenalan Pahlawan Berbasis Android - Satria Banureksa, Kezya; Parga Zen, Bita (Jurnal Informatika, 2024)
Learning media has a crucial role for teachers in conveying information during learning activities. However, many elementary schools currently still rely on audio-visual media and teaching aids, which can cause boredom among students during the teaching and learning process. Indonesian heroes are those who fought for Indonesian independence against the colonialists. Therefore, strategies are needed that can awaken feelings of love for the country and patriotism in children. It is hoped that the use of Android-based games as a learning medium can increase students' interest in learning, especially in understanding national heroes. The design of this multimedia application follows the Game Development Life Cycle (GDLC) method with initialization, preproduction, production, testing, beta and release stages. By designing this educational game, the author hopes to help students at SD Negeri 1 Karangsentul to get to know and remember Indonesia's national hero figures, as well as increase their sense of nationalism.